Implications of the Economic and Financial Crisis in South-East Europe - Andreea Gradinaru (CES Working Papers, 2013)
Initially triggered in the USA and generated by the chaos in the financial system of the country, the economic crisis has spread in Europe and, thanks to globalization, as a domino effect has spread around the world. Although the first part of 2008 South East Europe has lived with the belief that the countries in this region will be immune to the crisis, since September 2008, the situation has changed notably in these states. The purpose of this study is to describe the issues related to the economic crisis and its impacts on South-Eastern European countries. The first part of the study highlights economic and financial crisis origins, while in the second part the effects of the global crisis are presented and the last part states about implications of the crisis in South-Eastern Europe states.
Keywords: G01; E24; E31; O11; 330; South Eastern Europe; growth; economic crisis; unemployment rate Romania